115 KANSER HASTASINDA PORT KOMPLİKASYONLARININ DEĞERLENDİRİLMESİ - SAMANCI, Tülay; MOLİNAS MANDEL, Nil and BOZKURT, A. Kürşat and KUTLU, Fikret and URAS, Cihan (Cerrahpaşa Medical Journal, 2019)
Background.- This study was conducted to evaluate complications associated with venous access devices used in long-term therapies in the cancer patients. Methods.- One hundred and fifteen consequtive adult cancer patients in whom a subcutaneous port was inserted were evaluated retrospectively between 1996 and 2004. Results- The total accrued sum of device-days for the 115 ports studied was 62,004 days, the average duration after placement was 539 days (range,8-2348 days), and the median duration was 382 days. Complications were identified in 11 of the 115 patients (9.5%). The average duration of ports in the complication group was 467 days (range, 8-1024 days) and median was 407 days. Complications included thrombosis (n:6; 5.1%) in which in one of the patients the catheter end was found in the right femoral vein instead of right atrium causing deep venous thrombosis, port infection (n:1; 0.8%), pneumothorax (n:1; 0.8%), mediastinal extravasation (n:1; 0.8%), port occlusion (n:1; 0.8%) and breaking of the catheter of the port (n:1; 0.8%). Port removal as a result of the complication was performed in 7 patients. Conclusions.- The insertion technique and maintenance of sterility and safety is very important in long term intravenous access devices used in long term therapies in the cancer patients.